Frequent Constriction-Like Echocardiographic Findings in Elite Athletes Following Mild COVID-19: A Propensity Score-Matched Analysis - Lakatos, Bálint Károly; Tokodi, Márton; Fábián, Alexandra; Ladányi, Zsuzsanna; Vágó, Hajnalka; Szabó, Liliána; Sydó, Nóra; Csulak, Emese; Kiss, Orsolya; Babity, Máté; Kiss, Anna Réka; Gregor, Zsófia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The cardiovascular effects of SARS-CoV-2 in elite athletes are still a matter of debate. Accordingly, we sought to perform a comprehensive echocardiographic characterization of post-COVID athletes by comparing them to a non-COVID athlete cohort. Methods: 107 elite athletes with COVID-19 were prospectively enrolled (P-CA; 23±6 years, 23% female) 107 healthy athletes were selected as a control group using propensity score matching (N-CA). All athletes underwent 2D and 3D echocardiography. Left (LV) and right ventricular (RV) end-diastolic volumes (EDVi) and ejection fractions (EF) were quantified. To characterize LV longitudinal deformation, 2D global longitudinal strain (GLS) and the ratio of free wall versus septal longitudinal strain (FWLS/SLS) were also measured. To describe septal flattening (SF – frequently seen in P-CA), LV eccentricity index (EI) was calculated. Results: P-CA and N-CA athletes had comparable LV and RVEDVi (P-CA vs N-CA; 77±12 vs. 78±13mL/m2; 79±16 vs 80±14mL/m2). P-CA had significantly higher LVEF (58±4 vs 56±4%, p<0.001), while LVGLS values did not differ between P-CA and N-CA (-19.0±1.9 vs -18.8±2.2%). EI was significantly higher in P-CA (1.13±0.16 vs 1.01±0.05, p<0.001), which was attributable to a distinct subgroup of P-CA with a prominent SF (n=35, 33%), further provoked by inspiration. In this subgroup, the EI was markedly higher compared to the rest of the P-CA (1.29±0.15 vs 1.04±0.08, p<0.001), LVEDVi was also significantly higher (80±14 vs 75±11 mL/m2, p<0.001), while RVEDVi did not differ (82±16 vs 78±15mL/m2). Moreover, the FWLS/SLS ratio was significantly lower in the SF subgroup (91.7±8.6 vs 97.3±8.2, p<0.01). P-CA with SF experienced symptoms less frequently (1.4±1.3 vs. 2.1±1.5 symptom during the infection, p=0.01). Conclusions: Elite athletes following COVID-19 showed distinct morphological and functional cardiac changes compared to a propensity score-matched control athlete group. These results are mainly driven by a subgroup, which presented with some echocardiographic features characteristic of constrictive pericarditis.